2023
DOI: 10.1155/2023/8414040
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between SMADs and Colorectal Cancer Expression, Prognosis, and Immune Infiltrates

Abstract: Background. In recent years, the incidence and mortality of colorectal cancer (CRC) are increasing, and the 5-year survival rate of advanced metastatic CRC is poor. Small mothers against decapentaplegic (SMAD) superfamily are intracellular signal transduction proteins associated with the development and prognosis of a variety of tumors. At present, no study has systematically analysed the relationship between SMADs and CRC. Methods. Here, R3.6.3 was used to analyse the expression of SMADs in pan-cancer and CRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Carcinoembryonic antigen-associated cell adhesion molecule 5 (CEACAM5), a highly glycosylated protein of the CEACAM family, reduces the expression of TGF-β pathway members (TGFBR2, SMAD4, and SPTBN1), which alters the colonic microbiome to promote CRC [40]. By contrast, SMAD2 mutations have been reported in hepatocellular carcinoma (HCC) [41]. For SMAD4, about 70% of esophageal adenocarcinoma (EAC) associated with Barrett's esophagus (BE) revealed loss of heterozygosity in a region involving SMAD2 and SMAD4 on chromosome 18q [42,43].…”
Section: Role Of Tgf-β Signaling In the Carcinogenesis And Progressio...mentioning
confidence: 99%
“…Carcinoembryonic antigen-associated cell adhesion molecule 5 (CEACAM5), a highly glycosylated protein of the CEACAM family, reduces the expression of TGF-β pathway members (TGFBR2, SMAD4, and SPTBN1), which alters the colonic microbiome to promote CRC [40]. By contrast, SMAD2 mutations have been reported in hepatocellular carcinoma (HCC) [41]. For SMAD4, about 70% of esophageal adenocarcinoma (EAC) associated with Barrett's esophagus (BE) revealed loss of heterozygosity in a region involving SMAD2 and SMAD4 on chromosome 18q [42,43].…”
Section: Role Of Tgf-β Signaling In the Carcinogenesis And Progressio...mentioning
confidence: 99%
“…The earliest trigger is APC inactivation [ 2 ]. Mutations in other suppressor genes ( SMAD2 , SMAD4 [ 3 ], DCC [ 4 ], and TP53 [ 5 ]), oncogenes ( KRAS [ 6 ] and BRAF [ 7 ]), and other genes contribute to neoplastic transformation in foci of the altered colon mucosa, which in turn leads to further degeneration toward malignancy. Next-generation sequencing revealed that ARID1A (AT-rich interactive domain 1A) is one of the most frequently mutated genes in CRC [ 8 ].…”
Section: Introductionmentioning
confidence: 99%